Capacitación ambiental y mejoramiento de los servicios ecoturísticos, en el sector Tingana - Amasifuén Pérez, Alexander (2011)
Environmental education aims fonning citizens who know the scope biophysical and its associated problems; that they know how to help solve them and motívate them to enable them to participate in the solution, as well along with the ecotourisrn services has become an extraordinary source of income for people who develop in a sustainable manner, have a beneficial effect on improvíng the lífe qualíty of our communities through responsíble tourism initiatives seek to preserve the environment, protect fragile ecosystems, and promote the sustainable use ofthe biodiversity. The objective of this study is to strengthen knowledge and attitudes in the delívery of services in the ecotourism sector Tingana, this sector located in the area called Area of Conservation and Recovery of wetland ecosystems of the High May- ZOCRE HAM, in order to provide infonnation and suitable conditions for tourists as policies of a sustainable management of the area. In the present study used methods are applied, so that it is intended to modify the levels of significant leaming, arguing that the applied research seeks to know to do, to act, to build, to modify. In the case generate actions toward the ecotourism development Association and conservation of the Aguajal Renacal Avisado River-Tingana (ADECAR), taking into account that the area is an ecosystem of aguajales and renacales. In addition, the study presents a proposal to implement the ecotourism services through the creation of an interpretation center which is attempting to translate and adapt the technical language, and often complex of the environment, to a more infonnative and motivating that can be understood by a public medium, without losing their meaning and accuracy, as well as containers for the segregation ofthe solid waste and tags in the Tingana sector, this represents a tool oftourism management ofthe ZOCRE HAM.